Student Computational Thinking in Solving Sequence Problems Based on Learning Styles - Miswanto Miswanto; Toto Nusantara; Abdur Rahman As'ari; Sukoriyanto Sukoriyanto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The purpose of this study is to describe students' computational thinking in solving sequence problems based on learning styles. This research approach is qualitative research with exploratory and descriptive research types. The subjects in this study were students majoring in Mathematics Tadris, Fakultas Tarbiyah dan Ilmu Keguruan UIN SATU Tulungagung semester 5. First, students' computational thinking in solving sequence problems based on assimilation and convergent learning styles, including incoherent, complete, and systematic. Second, students' computational thinking in solving sequence problems based on assimilation and accommodation learning styles, including coherent, complete, and systematic. Third, students' computational thinking in solving sequence problems is based on convergent learning styles and accommodation, including coherent, complete, and unsystematic. Fourth, students' computational thinking in solving sequence problems is based on divergent and convergent learning styles, including incoherent, incomplete, and unsystematic.